Hubungan Antara Pemilihan Genre Musik dan Mood Setelah Mendengarkan Musik di Kalangan Mahasiswa Yogyakarta - Eben Firdaus Sipayung; Qharnozi Arief Irsyad (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
Music plays an important role in students’ daily lives, not only as a form of entertainment but also as a medium for emotional regulation and mood management. Preferences for certain music genres are often closely related to listeners’ psychological conditions and are used as a strategy to reduce stress and enhance emotional comfort. This study aims to examine the relationship between music genre selection and mood after listening to music among university students in Yogyakarta. This research employs a quantitative approach using a survey method. The research population consists of students from several universities in Yogyakarta, with a sample of 100 respondents selected using the Slovin formula and purposive sampling technique. Data were collected through a Likert-scale questionnaire measuring music preference as the independent variable and mood changes as the dependent variable. Data analysis was conducted using normality tests, linearity tests, correlation analysis, and simple regression analysis. This study is grounded in Mood Management Theory, which explains that individuals consciously select media, including music, to regulate and stabilize their emotional states. The findings of this study are expected to provide empirical insights into the role of music preferences in influencing students’ mood changes, as well as contribute theoretically to communication psychology studies and practically to student mental health management.